Identificación de una proteína ribosomal con actividad antimicrobiana, producida por Streptomyces lividans TK24 - Calderón de la Sancha, Fernanda Jocely (Universidad Autónoma Metropolitana, 2023)
The use of antimicrobial proteins and peptides is considered an alternative to replace traditional antibiotics that are currently ceasing to be effective in the presence of resistant pathogenic microorganisms. These molecules are effective against a broad spectrum of infectious bacterial, viral, fungal, and parasitic pathogens. The development of this project originated from the discovery of an antimicrobial compound around 10 kDa, this molecule was found in the biomass-free extract of a Streptomyces lividans TK24 culture. In the first stage we showed that this molecule contained in ELB acts against Bacillus subtilis, Bacillus cereus, Kokuria rhizophila, Clostridium sporogenes and Clavibacter michiganensis (phytopathogenic bacteria responsible for bacterial canker), all these bacteria are Grampositive. Antimicrobial activity was observed only when glycerol and glucose were used as carbon source. As a second stage a partial protein purification was performed, starting with ammonium sulfate precipitation followed by ion exchange chromatography, then hydroxyapatite chromatography. By SDS-PAGE gel (under non-denaturing conditions) coupled to an antimicrobial activity assay, it was determined that the band with antimicrobial activity corresponds to a size of 12.6±1.26 kDa. On the other hand, by liquid chromatography coupled with tandem mass spectrometry, we identified that 11 proteins were within the interval of 11.3-13.9 kDa. Through a functional analysis we selected 4 proteins as those possibly responsible for the antimicrobial activity. In stage three, a gene expression analysis was made to determine the expression levels of the genes that code for the selected proteins and see the relationship with the antimicrobial activity, using culture conditions that showed antimicrobial activity and culture conditions that did not show antimicrobial activity. Altogether, protein fractionation, correlation analysis between antimicrobial activity and abundance of selected proteins, as well as gene expression (semi-quantitative and quantitative analyses) and a prediction of the antimicrobial potential of peptides, indicate that the 50S ribosomal protein L19 is the main candidate responsible for the antimicrobial activity. Keywords: Antimicrobial protein; moonlighting protein; Streptomyces lividans; Clavibacter michiganensis.; El uso de proteínas y péptidos antimicrobianos se considera una alternativa para sustituir a los antibióticos tradicionales que actualmente están dejando de ser efectivos ante la presencia de microorganismos patógenos resistentes. Estas moléculas son efectivas hacia un amplio espectro de patógenos bacterianos, virales, fúngicos y parasitarios. El desarrollo de este proyecto surgió por el descubrimiento de un compuesto con actividad antimicrobiana mayor a 10 kDa, dicha molécula se encontró en el extracto libre de biomasa (ELB) de un cultivo de Streptomyces lividans TK24. En la primera etapa demostramos que esta molécula contenida en el ELB actúa contra Bacillus subtilis, Bacillus cereus, Kokuria rhizophila, Clostridium sporogenes y Clavibacter michiganensis (bacteria fitopatógena responsable del cancro bacteriano), todas son bacterias Gram-positivas, y que la actividad antimicrobiana se presentaba solo cuando se utilizaba glicerol y glucosa como fuente de carbono. En la segunda etapa se realizó una purificación parcial de proteínas, iniciando con una precipitación con sulfato de amonio seguida de cromatografía de intercambio iónico y una cromatografía con hidroxiapatita. Mediante gel SDS-PAGE (en condiciones no desnaturalizantes) acoplado a una prueba de actividad antimicrobiana se determinó que la banda con actividad antimicrobiana corresponde a un tamaño de 12.6±1.26 kDa. Por otro lado, mediante cromatografía líquida acoplada a espectrometría de masas en tándem identificamos que 11 proteínas se encontraban dentro del intervalo de 11.3-13.9 kDa. A través de un análisis funcional seleccionamos 4 proteínas como las posibles responsables de la actividad antimicrobiana. En la etapa 3 se hizo un análisis de expresión génica para determinar los niveles de expresión de los genes que codifican a las proteínas seleccionadas y ver la relación con la actividad antimicrobiana, empleando condiciones de cultivo que mostraron actividad antimicrobiana y condiciones de cultivo que no mostraron actividad antimicrobiana. En conjunto, el fraccionamiento de proteínas, el análisis de correlación entre la actividad antimicrobiana y la abundancia de las proteínas seleccionadas, el análisis de expresión génica (análisis semicuantitativo y cuantitativo) y una predicción del potencial antimicrobiano de péptidos, indican que la proteína 50S ribosomal L19 es la principal candidata responsable de la actividad antimicrobiana. Palabras clave: Proteína antimicrobiana; proteínas moonlighting; Streptomyces lividans; Clavibacter michiganensis.